Investigation of small RNA communication in the mutualistic interaction of Serendipita indica and Arabidopsis thaliana - Nasfi-Moses, Sabrine; Justus Liebig University Giessen (My University, 2026)
Interactions between plants and their symbiotic partners are characterised by complex molecular mechanisms that promote symbiont and plant growth, nutrient uptake, and stress tolerance. Despite the established role of small RNAs (sRNAs) in regulating gene expression in eukaryotes, further investigation is required to understand their contribution to this beneficial exchange. In this work, we investigated whether the beneficial endophyte Serendipita indica (Si), with its large host range, uses sRNA-mediated cross-kingdom (ck) communication with plant hosts. Sequencing of sRNA from S.indica cultivated in axenic culture and during its interaction with Brachypodium distachyon provided first evidence of ckRNA communication between plants and their mutualistic fungi and identified putative S.indica sRNAs (SisRNA). To explore the molecular basis of ck-RNA interference (RNAi) in mutualism, we developed a pipeline to investigate the role of SisRNAs during S. indica colonisation of Arabidopsis thaliana (At). The expression of SisRNAs was validated in Si-colonised At roots. SisRNAs were overexpressed in a protoplast transient system, and their accumulation was confirmed. The potential of SisRNAs to induce post-transcriptional gene silencing (PTGS) of predicted At target genes was investigated, and downregulation of genes involved in cell wall organisation, hormone signalling, and immunity was observed. Immunoprecipitation (IP) of Argonaute 1 (AGO1) from Si-colonised At roots, followed by western-blot analysis and stem-loop PCR, confirmed the translocation of SisRNAs into At roots and their loading into the plant RNAi machinery. Additionally, sRNA sequencing of AGO1- and AGO2-bound sRNA recovered after IP identified 18 to 26 nt SisRNAs being loaded into AGO1 and AGO2 in Si-colonised At roots with diverse 5´-ends. The role of Arabidopsis RNAi machinery in regulating symbiosis and colonisation was examined by analysing S. indica growth on Arabidopsis DICER-LIKE (DCL) and AGO mutants, as well as AGO expression profiling of At Col-0 S. indica colonised roots. The results demonstrated that AGO2 and AGO10, but not AGO1, function as positive regulators, suggesting specialised and potentially redundant functions of AGO proteins in mutualistic interactions. S.indica extracellular vesicles (EV)-like particles were isolated from S.indica liquid cultures. EV-like structures with cup-shaped morphology were observed, and SisRNAs previously associated with the Si-At interaction were detected in the vesicle fraction, suggesting a possible role for S.indica EVs in RNA transport, but further investigations are needed. Taken together, this work reveals that mutualistic fungi can use sRNAs to regulate host gene expression by exploiting plant RNAi machinery and provides genomic and molecular hints for ck-RNA communication in mutualistic symbioses.
Keywords: ddc:570; ddc:630